2002
DOI: 10.1093/jhered/93.5.323
|View full text |Cite
|
Sign up to set email alerts
|

African-Derived Mitochondria in South American Native Cattle Breeds (Bos taurus): Evidence of a New Taurine Mitochondrial Lineage

Abstract: This article reports the nucleotide diversity within the control region of 42 mitochondrial chromosomes belonging to five South American native cattle breeds (Bos taurus). Analysis of these data in conjunction with B. taurus and B. indicus sequences from Africa, Europe, the Near East, India, and Japan allowed the recognition of eight new mitochondrial haplotypes and their relative positions in a phylogenetic network. The structure of genetic variation among different hypothetical groupings was tested through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
2
32
0
1
Order By: Relevance
“…Although it is generally assumed that gene flow between and within zebu and taurine cattle and crosses thereof have been intense in Brazil, there is a lack of information on gene flow quantification and breed relationships among Brazilian cattle. Miretti et al (2002) did not find any zebu mtDNA haplotype in taurine cattle breeds descendant from cattle that were introduced in South America some 500 years ago by Portuguese and Spanish colonizers. Yet, Meirelles et al (1999) found taurine mtDNA in 59 of 102 samples of Gir and Nelore breeds, which was consistent with the known matrilinear contribution of the taurine cattle originally introduced in Brazil, for the formation of the modern Brazilian zebu.…”
Section: Introductionmentioning
confidence: 65%
“…Although it is generally assumed that gene flow between and within zebu and taurine cattle and crosses thereof have been intense in Brazil, there is a lack of information on gene flow quantification and breed relationships among Brazilian cattle. Miretti et al (2002) did not find any zebu mtDNA haplotype in taurine cattle breeds descendant from cattle that were introduced in South America some 500 years ago by Portuguese and Spanish colonizers. Yet, Meirelles et al (1999) found taurine mtDNA in 59 of 102 samples of Gir and Nelore breeds, which was consistent with the known matrilinear contribution of the taurine cattle originally introduced in Brazil, for the formation of the modern Brazilian zebu.…”
Section: Introductionmentioning
confidence: 65%
“…The mutational dynamics of mtDNA sequences enable the genetic relationships among haplotypes to be inferred. Argentinean Creole (n=12) and Brazilian native cattle breeds Pé-duro (n= 11), Caracu (n=8), Mocho Nacional (n=6) and Pantaneiro (n=10) were analyzed according to Miretti et al (2002). Details regarding PCR amplification, sequencing reactions and primers sequence were previously reported by Miretti et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…MtDNA control region polymorphisms have been reported in American Creole cattle breeds from several North, South, Central and Caribbean countries (Magee et al, 2002;Miretti et al, 2002Miretti et al, , 2004Carvajal-Carmona et al, 2003;Mirol et al, 2003;Lirón et al, 2006a;Ginja et al, 2010). These studies reported the existence of European T3, African T1, and Middle Eastern T2 haplotypes.…”
Section: Introductionmentioning
confidence: 94%
“…These studies reported the existence of European T3, African T1, and Middle Eastern T2 haplotypes. African haplotypes in America, were also identified as belonging to two different sub-haplogroups, T1* and T1a (AA1 in Miretti et al, 2002 nomenclature;Miretti et al, 2002Miretti et al, , 2004Lirón et al, 2006a). In addition, the patrilinages present in Creole cattle were analyzed through Y chromosome microsatellites and single nucleotide polymorphisms (SNPs) (Giovambattista et al, 2000;Ginja et al, 2010).…”
Section: Introductionmentioning
confidence: 99%